Feedback as a means to improve clinical competencies: Consultants’ perceptions of the quality of feedback given to registrars - Chauntelle Bagwandeen; Veena Singaram (South African Medical Association, 2016)
Background. Effective supervision by consultants in postgraduate medical education involves the process of feedback. Giving feedback may be challenging for consultants who have no formal training in this process, which may be further compounded in heterogeneous diverse settings. Objective. To explore consultants’ perceptions of feedback to registrars in a multicultural, multilingual diverse academic hospital setting. Methods. Thirty-seven consultants consented to completing a questionnaire on what, when, where, how often, and how feedback was provided, as well as on the type and effect of feedback to registrars. Descriptive statistics were used to analyse the data. Differences between groups were calculated using Pearson’s χ² test for independent variables, with a p-value of <0.05 regarded as being statistically significant. Results. Only 40% of consultants reported that they provided feedback often or always and 62.2% reported that standards were not predetermined and communicated to registrars. When feedback was provided, it was based on concrete observations of performance (78.4%), it incorporated a plan for improvement (72.9%) and it supplied information on techniques performed incorrectly (72.9%). Only 40.5% of consultants provided feedback on procedures performed correctly. Moreover, only half of the consultants believed they were proficient at giving feedback. Conclusion. Consultants need to develop the art of giving feedback through appropriate training so that they are more comfortable and proficient with the various aspects of feedback, leading to a positive effect on enhancing registrar training.